Thermal Therapy Modulation of the Psoriasis-Associated Skin and Gut Microbiome - Serena Manara; Francesco Beghini; Giulia Masetti; Federica Armanini; Davide Geat; Giulia Galligioni; Nicola Segata; Stefania Farina; Mario Cristofolini (Dermatology and Therapy, 2023)
Abstract Introduction Psoriasis is a systemic immune-mediated disease primarily manifesting as skin redness and inflammation. Balneotherapy proved to be a successful non-pharmacological option to reduce the skin areas affected by the disease, but the specific mechanisms underlying this effect have not been elucidated yet. Here we test the hypothesis that the effect of thermal treatments on psoriatic lesions could be partially mediated by changes in the resident microbial population, i.e., the microbiome. Methods In this study, we enrolled patients with psoriasis and monitored changes in their skin and gut microbiome after a 12-bath balneotherapy course with a combination of 16S rRNA amplicon sequencing and metagenomics. Changes in the resident microbiome were then correlated with thermal therapy outcomes evaluated as changes in Psoriasis Area and Severity Index (PASI) and Body Surface Area index (BSA). Results The amplicon sequencing analysis of the skin microbiome showed that after thermal treatment the microbiome composition of affected areas improved to approach that typical of unaffected skin. We moreover identified some low-abundance bacterial biomarkers indicative of disease status and treatment efficacy, and we showed via metagenomic sequencing that thermal treatments and thermal water drinking affect the fecal microbiome to host more species associated with favorable metabolic health. Conclusions Changes in lower-abundance microbial taxa presence and abundance could be the basis for the positive effect of thermal water treatment and drinking on the cutaneous and systemic symptomatology of psoriasis.